2020
DOI: 10.2147/ott.s242820
|View full text |Cite
|
Sign up to set email alerts
|

<p>β-Elemene Enhances the Chemotherapeutic Effect of 5-Fluorouracil in Triple-Negative Breast Cancer via PI3K/AKT, RAF-MEK-ErK, and NF-κB Signaling Pathways</p>

Abstract: Background:The most common chemotherapeutic drug for triple-negative breast cancer (TNBC) treatment is 5-fluorouracil (5-FU), but its therapeutic index is low due to its toxicity. β-Elemene (ELE) possesses antitumor activity against different cancers, but it has never been used in combination with 5-FU to improve its chemotherapeutic effect against TNBC. Materials and Methods: We treated MDA-MB-231 and BT549 cells of TNBC with ELE alone, 5-FU alone, or their combination to investigate their treatment effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…Further studies are required in detail to warrant any conclusion. Fluorouracil (5-FU) is used as a single palliative treatment in combination with other antineoplastic agents for the therapy of breast cancers 69 . According to National Comprehensive Cancer Network guidelines, 5-fluorouracil, epirubicin and cyclophosphamide (FEC) adjuvant chemotherapy regimen is the recommended regimen for breast cancer 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are required in detail to warrant any conclusion. Fluorouracil (5-FU) is used as a single palliative treatment in combination with other antineoplastic agents for the therapy of breast cancers 69 . According to National Comprehensive Cancer Network guidelines, 5-fluorouracil, epirubicin and cyclophosphamide (FEC) adjuvant chemotherapy regimen is the recommended regimen for breast cancer 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies (Ahn, Sethi, & Aggarwal, 2008;Dana, Vaseghi, & Haghjooy Javanmard, 2020;M. Deng, Dai, Yu, Tao, & Lung, 2020;Fu et al, 2020;Ghasemi et al, 2019;Khalil et al, 2020;Monisha et al, 2017;Morgan, Garg, Tergaonkar, Tan, & Sethi, 2020;Su, Ahmad, Zou, & Zou, 2020;Xiaomeng et al, 2020;Zou, Hu, & Jiang, 2020) have confirmed that NF-κB is a key regulator of stress and inflammation, participates in cell proliferation and apoptosis, and is important in signal transduction during tumorigenesis and progression. Oleuropein reduced the expression of nuclear factor-kappa Β (NF-κB) in different tumor models (Elamin et al, 2019;Giner et al, 2016;L.…”
Section: Nuclear Factor-kappa βmentioning
confidence: 99%
“…Even though 5-FU is not a key drug in the current clinical scenario of breast cancer chemotherapy, it is used either alone or in combination with other drugs for the successful treatment and management of metastatic breast cancer (50). Recent reports also demonstrate that 5-FU can be used either alone or in combination with other drugs to treat triple negative breast cancer effectively (51,52). Though numerous studies have demonstrated the anticancer potential of curcumin against various cancers, none of the clinical trials conducted using this phytochemical has generated substantial outputs.…”
Section: Discussionmentioning
confidence: 99%